The miR-199a-3p regulates the radioresistance of esophageal cancer cells via targeting the AK4 gene - Chunbao Zang; Fangfang Zhao; Lei Hua; Youguang Pu (Cancer Cell International, 2018)
Abstract Background MiRNAs was recognized as vital regulators involved in cancer development. Radioresistance remains a major obstacle for effective treatment of cancers. The mechanisms on the miRNA-mediated radioresistance of cancers are still poorly understood. The main subject of this study is to find new miRNA biomarker that regulates the radioresistance of esophageal cancer (EC). Methods The cumulative dose of radiation assays were used to screen the EC radioresistant cell lines. Wound-healing and invasion assays were used to characterize the properties of these cell lines. The following survival fraction experiments were performed to test the effects of miR-199a-3p and AK4 in the radioresistance of EC. In addition, we used the luciferase reporter assays to identify the putative underlying mechanism that relates to the miR-199a-3p regulated radio-resistance. Results We found that the AK4 gene is one of the targets of miR-199a-3p, which promotes the radioresistance of EC cells. The following experiments by force reversal of the miR-199a-3p or AK4 levels confirmed the relationship of miR-199a-3p and AK4 with the radioresistance of EC cells. In addition, the activities of several signaling pathway were drastically altered by the forced changes of the miR-199a-3p level in EC cells. Conclusion Taken together, we found that miR-199a-3p can be potentially used as a biomarker for the EC radioresistance. Moreover, these results provides new insights into the mechanism on the radioresistance of EC cells, and also might guide the clinical therapy of EC.